ANALISIS KONDISI KERUSAKAN JALAN MENGGUNAKAN METODE PAVEMENT CONDITION INDEX (PCI) DAN INTERNATIONAL ROUGHNESS INDEX (IRI) BESERTA ALTERNATIF PENANGANANNYA (Studi Kasus: Jalan Samaun Pulubuhu - Jalan Boliohuto Huidu - Jalan A.K. Luneto) - herris julian Koromath; Frice L Desei; Yuliyanti Kadir (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
Samaun Pulubuhu Street - Boliohuto Huidu Street - A.K. Luneto Street is one of the roads connecting Gorontalo City, Djalaludin Airport, and surrounding districts in Gorontalo Province. This study aims to compare the value of road conditions based on the PCI and IRI methods and determine the alternative treatments.This study uses the Pavement Condition Index (PCI) and International Roughness. Index (IRI) methods. The PCI value is obtained through a direct visual survey of road conditions. The IRI value was obtained through a survey using a car and the Roadlab Pro application.The results show that the condition of the roads based on the PCI method is excellent 19.44%, very good 8.8%, good 14.81%, moderate 18.06%, bad 17.13%, very bad 10.65%, and failed 11.11%. Meanwhile, road conditions based on the IRI method are good 3.13%, moderate 64.06%, lightly damaged 21.09%, and heavily damaged 11.72%. The PCI value on Samaun Pulubuhu Street is 52.48 in moderate condition with the type of treatment needed is minor rehabilitation, on Boliohuto Huidu Street is 61,53 in good condition with the type of treatment needed is routine maintenance, and on A.K. Luneto Street is 23.98 in bad condition with the type of treatment needed is reconstruction. The IRI value on Samaun Pulubuhu Street is 8.42 in a slightly damaged condition with the type of treatment needed is road quality improvement, on Boliohuto Huidu Street - A.K. Luneto Street are 5.68 and 6.41 in moderate condition with the type of treatment needed is regular maintenance.